Correlation of serum visfatin level with chest pain scoring as an indication of myocardial ischemia in chronic kidney disease patients - Mohamed F Almaghraby; Abeer A Mahmoud (SpringerOpen, 2014)
Background Nicotinamide phosphoribosyltransferase (Visfatin), an enzyme involved in the NAD+ salvage pathway, has been shown to help in the regulation of glucose homeostasis. It is a highly conserved, 52 kDa protein found in living species from bacteria to humans. It is an adipokine produced and secreted primarily by adipose tissue. Chronic kidney disease (CKD) and end-stage renal disease patients showed increased cardiovascular mortality, and vascular events account for more than half of the deaths in this population. Myocardial ischemia is a consequence of coronary heart disease. Recent studies found that with increasing visfatin levels, CKD patients have a larger number of vessels with stenosis and a higher likelihood of coronary artery disease. Research design and methods The current prospective study includes 137 CKD patients and patients with chest pain (CP), as well as 20 patients as controls. Patient data included age, sex, comorbidities, smoking status, weight, height, and BMI, calculated using the equation: BMI = weight (kg)/height (m 2 ). Estimated glomerular filtration rate was calculated using the modified Modification of Diet in Renal Disease equations; in addition, enzyme-linked immunosorbent assay was used to estimate serum visfatin levels, and CP was assessed through a modification of the master questionnaire. Results All patients had significantly (P < 0.05) higher serum visfatin levels compared with controls. Patients who had typical anginal CP had significantly (P < 0.05) higher serum visfatin levels compared with those who had atypical anginal or nonanginal CP, with nonsignificantly (P > 0.05) higher serum visfatin levels in patients with atypical anginal CP compared with those with nonanginal CP. Moreover, patients with stage 4 CKD had a significantly (P < 0.05) higher serum visfatin level compared with patients with stage 3 CKD. Conclusion It could be concluded that patients with CKD are at an actual risk of developing CP secondary to myocardial ischemic attack, presenting either as typical or as atypical anginal pain. Elevated serum visfatin levels may be the cornerstone for the relationship between CKD and coronary heart disease. Serum visfatin levels in range of 12.4-16.4 ng/ml could predict the possibility of developing an anginal attack in patients with atypical anginal CP, with high sensitivity and specificity for diagnosis.